Simulation and Experimental Study for Electromagnetic Absorption in Sandstone with SrFeO3 Nanofluid - Ali, H. (Springer Science and Business Media B.V., 2021)
Electromagnetic absorption properties of sandstone saturated with Strontium ferrite (SrFeO3) nanofluid are discussed in this paper. The synthesis of nanoparticles was carried out using the solâgel combustion method and calcinated at a temperature of 300â400Â Â°C in a furnace. X-ray diffraction pattern verified the crystalline structure of SrFeO3, and FESEM images confirmed the morphology of nanoparticles. The dielectric and magnetic studies were carried out using the vector network analyzer (VNA) to measure the dielectric losses in dry sandstone and the sandstone saturated with SrFeO3 nanofluids. Comparative analysis of the electric permittivity, complex permittivity, and the dielectric losses of sandstone with SrFeO3 provided an insight about the microwave absorbing properties. Simulations of these materials with electromagnetic field verified experimental results, as SrFeO3 has the greater capacity to absorb the electromagnetic waves and can be used as a potential material for enhanced oil recovery. Â© 2021, The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd.